Performa Badan Amil Zakat selama Pandemi COVID-19, Ada yang Berbeda: Kilasan dari BAZNAS Sinjai Sulawesi Selatan - Anriani .; Agusdiwana Suarni; Muhammad Khaedar Sahib (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
Covid-19 pandemic creates the climate change of work in various sector, one of them is National Amil Zakat Agency (BAZNAS). This research aims to disclose the performance of BAZNAS during the pandemic. This research was conducted in the National Amil Zakat Agency (BAZNAS) office in Sinjai Regency. This type of research was qualitative with a case study method. The data collection method used was observation, interviews and documentation. The informant this research consisted of two people the executive of BAZNAS Sinjai and three people of Muzakki. The result of this research demonstrates that BAZNAS conducts the zakat pick-up service and maximizes the performance through online services within paying and collecting of zakat, infaq, and shadaqah for the Covid-19 pandemic age. In addition, strategies of campaign and communication to society is undertaken by utilizing online media platforms such as Whatsapp, Facebook, and Twitter. Over the pandemic age. The use of the platform and online service over the pandemic age actually increases the receipt of zakat, infaq, and shadaqah in BAZNAS Sinjai